2019
DOI: 10.1002/brb3.1244
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of freezing of gait in Parkinson's disease patients

Abstract: Objective To clarify the clinical features of freezing of gait (FOG) in Parkinson's disease (PD) patients by classification into two groups: Clinically observed FOG (CFOG) and self‐reported FOG (SFOG). Methods Two hundred twenty‐nine PD patients were medically examined in an examination room as well as subjected to a New Freezing of Gait Questionnaire (NFOG‐Q) and analysis of nonmotor symptoms including sleep, cognition, depression, and fatigue. Results The prevalence of CFOG was 17.9%, while 53.7% of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
6
19
0
1
Order By: Relevance
“…As anticipated, advanced PD patients could have more severe motor performance and higher H&Y scales. Depression is considered to be related to FOG in PD patients (37). Our results consistently showed that the PD+FOG group had mild depression on average, while the PD-FOG group had a relatively normal GDS scores.…”
Section: Discussionsupporting
confidence: 74%
“…As anticipated, advanced PD patients could have more severe motor performance and higher H&Y scales. Depression is considered to be related to FOG in PD patients (37). Our results consistently showed that the PD+FOG group had mild depression on average, while the PD-FOG group had a relatively normal GDS scores.…”
Section: Discussionsupporting
confidence: 74%
“…We found FOG in PD to be unrelated to sex and only weakly associated with patient age, consistent with the majority of other prospective studies [ 4 , 8 , 10 12 , 30 ]. On the other hand, supporting extensive literature, we found disease duration to be strongly associated with FOG [ 4 7 , 9 , 12 , 13 , 31 ]. One previous prospective study failed to show an association between disease duration and incident FOG [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…One difference relates to the commencement of FOG where Gilat defined FOG starting when the foot no longer takes an effective step, whereas we took the last heel strike of the last full step as the FOG commencement point as it is easier to precisely identify. A further strength is the use of the gold standard method of video recordings with ancillary reference to synchronised accelerometry data to classify freezing episodes [19,45]. Thus, given the assessments included cognitive and motor factors known to induce FOG episodes, the incidence and nature of the freezes and other gait disturbances observed should generalise well to those experienced in everyday life.…”
Section: Strengths and Limitationsmentioning
confidence: 99%